Molecular characterization of intestinal protozoa in two poor communities in the State of São Paulo, Brazil - David, Érica Boarato; Guimarães, Semíramis; de Oliveira, Ana Paula; Goulart de Oliveira-Sequeira, Teresa Cristina; Nogueira Bittencourt, Gabriela; Moraes Nardi, Ana Rita; Martins Ribolla, Paulo Eduardo; Bueno Franco, Regina Maura; Branco, Nilson; Tosini, Fabio; Bella, Antonino; Pozio, Edoardo; et al. (Parasites & vectors, 2015)
BACKGROUND: Several species of protozoa cause acute or chronic gastroenteritis in humans, worldwide. The burden of disease is particularly high among children living in developing areas of the world, where transmission is favored by lower hygienic standards and scarce availability of safe water. However, asymptomatic infection and polyparasitism are also commonly observed in poor settings. Here, we investigated the prevalence of intestinal protozoa in two small fishing villages, Porto Said (PS) and Santa Maria da Serra (SM), situated along the river Tietê in the State of São Paolo, Brazil. The villages lack basic public infrastructure and services, such as roads, public water supply, electricity and public health services. METHODS: Multiple fecal samples were collected from 88 individuals in PS and from 38 individuals in SM, who were asymptomatic at the time of sampling and had no recent history of diarrheal disease. To gain insights into potential transmission routes, 49 dog fecal samples (38 from PS and 11 from SM) and 28 river water samples were also collected. All samples were tested by microscopy and PCR was used to genotype Giardia duodenalis, Blastocystis sp., Dientamoeba fragilis and Cryptosporidium spp. RESULTS: By molecular methods, the most common human parasite was Blastocystis sp. (prevalence, 45% in PS and 71% in SM), followed by D. fragilis (13.6% in PS, and 18.4% in SM) and G. duodenalis (18.2% in PS and 7.9% in SM); Cryptosporidium spp. were not detected. Sequence analysis revealed large genetic variation among Blastocystis samples, with subtypes (STs) 1 and 3 being predominant, and with the notable absence of ST4. Among G. duodenalis samples, assemblages A and B were detected in humans, whereas assemblages A, C and D were found in dogs. Finally, all D. fragilis samples from humans were genotype 1. A single dog was found infected with Cryptosporidium canis. River water samples were negative for the investigated parasites. CONCLUSIONS: This study showed a high carriage of intestinal parasites in asymptomatic individuals from two poor Brazilian villages, and highlighted a large genetic variability of Blastocystis spp. and G. duodenalis.